STRATEGI PEMBERDAYAAN PKK MELALUI PROGRAM DAUR EKONOMI SIRKULAR DENGAN PENDEKATAN SOSIAL MEDIA - Berliana Rifty, Kelsha (ISB Atma Luhur, 2025)
This research aims to develop an empowerment strategy for Family Welfare Movement (PKK) members through a circular economy-based waste recycling program supported by a social media approach. In the context of the increasing problem of environmental pollution caused by plastic waste, empowering the PKK as a community group has significant potential to manage plastic waste through innovative eco-friendly fashion products. This program adopts circular economy principles by processing plastic waste into useful products, such as eco-friendly tote bags. Social media is used as a strategic tool for education, promotion, and strengthening the marketing network for recycled products, thereby expanding market reach and increasing social inclusion. The research method combines a qualitative approach with market analysis, community engagement, and evaluating the effectiveness of social media use in empowerment. The results are expected to contribute to PKK empowerment in creating new, sustainable sources of income, while supporting plastic waste reduction through innovative and environmentally friendly products. The implications of this research also include strengthening the social, economic, and environmental aspects of community plastic waste management, which can be applied more broadly.